Від співу до публікації, перекладу та ілюстрацій: перероблені варіанти трьох скандинавських традиційних балад - Сіндергард, Л. (Народна творчість та етнологія, 2012)
Larry Syndergaard. From Song to Print, to Translation and Pictures: Rewritings of Three Scandinavian Traditional Ballads. During two centuries the traditional Scandinavian ballads and their translation have made a special cultural impact in the English-speaking world. By paying close attention to the series of collecting, editing, translation, and illustration rewritings of these ballads we can understand some of the uses to which we outside of the originating cultures have put the products of those cultures. Rewritings tend to have cultural agendas, which we need to identify and acknowledge. In the present paper, these include spiritual, nationalism, homophobia, and sexual propriety among others. A subsidiary purpose of the paper is to draw attention to illustrations of ballad translations as subjects overdue for scholarly discourse.